Interchangeability in Military Interprofessional Health Care Teams: Lessons Into Collective Self-healing and the Benefits Thereof. Issue 11 (26th October 2021) - Cristancho, Sayra; Field, Emily; Bader-Larsen, Karlen S; Varpio, Lara
ABSTRACT: Introduction: Interchangeability—i.e., the capacity to change places with another—is necessary for military interprofessional health care teams (MIHTs) to provide around-the-clock patient care. However, while interchangeability is clearly a necessity for modern health care delivery, it raises uncomfortable questions for civilian health care teams where it is usually labeled as unsafe. This perception surfaces because interchangeability runs counter to some of health care's cultural beliefs including those around patient ownership and professional scopes of practice. It is, therefore, not surprising that little is known about whether and how some level of interchangeability can be harnessed to improve the productivity of health care teams overall. In this article, we explore the notion of interchangeability in the particular context of MIHTs given that these health care teams are familiar with it. This exploration will offer insights into how interchangeability could maximize civilian health care teams' capacity to adapt. Materials and Methods: We conducted a secondary analysis of interview data as an analytic expansion: "the kind of study in which the researcher makes further use of a primary data set in order to ask new or emerging questions that derive from having conducted the original analysis but were not envisioned within the original scope of the primary study aims". Within our secondary analysis approach, we used thematic analysis as our analytical tool to describe (1) what interchangeability looks like in MIHT teams, (2) how it is fostered in MIHTs, and (3) how it is enacted in MIHTs. Results: Interchangeability was realized in MIHTs when individual team members adapted to take on roles and/or tasks that were not clearly niched in their specific areas of expertise but instead drew on the broad foundation of their clinical skill set. Cross-training and distributed leadership were ways in which MIHT members described how interchangeability was fostered. Furthermore, five features of working within MIHT teams were identified as key conditions to enact interchangeability: knowing your team members; being able to work with what/who you have; actively seeking others' expertise; situating your role within the broader picture of the mission; and maintaining a learning/teaching mindset. Conclusions: Interchangeability can be understood through the theoretical lens of Swarm Intelligence and more specifically, the principle of collective self-healing — which is the ability of collectives to continue to successfully perform despite disruption, challenges, or the loss of a team member. Our findings highlight how MIHTs have adopted interchangeability in a wide array of contexts to realize collective self-healing. Despite the discomfort it provokes, we suggest that interchangeability could be a powerful asset to civilian health care teams.